Pengaruh Sistem Pendidikan Pesantren Terhadap Pembinaan Moral Santri - Julika Rahma (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2021)
This research was conducted using a quantitative approach. Based on the data processing carried out, the pesantren education system is in the "Medium" category, with an average value of 56.12 then the moral development of students in the "Medium" category with an average value of 44.29, then the test results rxy = 0.791 with the category " Strong "there is a significant relationship between the pesantren education system on the moral development of students, the determinant coefficient (KD) is 62.6%, this indicates that the pesantren education system contributes 62.6% to the moral development of students. The regression equation Y = 59.49 + 0.489X means that every change in the score of the pesantren education system by 1 unit can be predicted that the score of students' moral development will increase by 0.489 units in the same direction, based on the hypothesis, data can be obtained using F count = 12,743 F table 3,991 at a significant level of 5%. This means that there is a significant influence between the pesantren education system on the moral development of students at the modern Al-Hasyimiyah Islamic Boarding School Darul Ulum, Halongonan District, North Padang Lawas Regency.